IMPORTANCE AND PERFORMANCE ANALYSIS OF PROMOTIONAL MIX IN INDOMARET POINT MANADO - Esterlita, Geruh D. N.; Pangemanan, Sifrid S.; Tumewu, Ferdinand J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2020)
This study aims to examine if there are significant effect of importance and performance analysis of promotional in Indomaret Point Manado. This study is a quantitative research by distributing quistionnaires using Likert Scale. The sample in this research is consisting of 100 respondents. The sampling was applied in this research regarding to obtain information according to customers who have purchases at Indomaret Point Manado. This research figured out consumer preference and perspective of which promotion is important to them and promotion that needs an improvement using IPA tool. With contributions of the customers of Indomaret Point Manado, the researcher answered the problem questions.Â  There were 100 questionnaires returned, and primary data acquired were all from the questionnaires include the characteristics of customers that have participated in this research such as gender, age, education background, occupation, working period and income. Based on research results and Importance and Performnce Analysis grip, researcher found that Indomaret Point Manado overall deliver not so good performance on promotion, because only five attributes in quadrant II, less than other importance attribute according to the customers.Â Keywords: Indomaret, promotional, importance and performance analysis